2020
DOI: 10.1016/j.actamat.2020.03.004
|View full text |Cite
|
Sign up to set email alerts
|

Ductile and brittle crack-tip response in equimolar refractory high-entropy alloys

Abstract: Understanding the strengthening and deformation mechanisms in refractory high-entropy alloys (HEAs), proposed as new high-temperature material, is required for improving their typically insufficient room-temperature ductility. Here, density-functional theory simulations and a continuum mechanics analysis were conducted to systematically investigate the competition between cleavage decohesion and dislocation emission from a crack tip in the body-centered cubic refractory HEAs HfNbTiZr, MoNbTaVW, MoNbTaW, MoNbTi… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(13 citation statements)
references
References 70 publications
0
13
0
Order By: Relevance
“…One approach uses extensive DFT calculations of a defect energy over many compositions and realizations followed by learning of the property trends, as demonstrated 37 for the USFE in bcc HEAs that is important for intrinsic ductility. [36][37][38] Another approach is to develop a similar DFT database to create a machine-learning interatomic potential, from which defect properties can be studied. Potentials are often aimed at the study one or a few properties, such as thermodynamics in the Cantor alloys, 39 the USFE in bcc alloys, 40 or dislocations in bcc MoNbTaW.…”
Section: Defects In the Presence Of High Chemical Disordermentioning
confidence: 99%
“…One approach uses extensive DFT calculations of a defect energy over many compositions and realizations followed by learning of the property trends, as demonstrated 37 for the USFE in bcc HEAs that is important for intrinsic ductility. [36][37][38] Another approach is to develop a similar DFT database to create a machine-learning interatomic potential, from which defect properties can be studied. Potentials are often aimed at the study one or a few properties, such as thermodynamics in the Cantor alloys, 39 the USFE in bcc alloys, 40 or dislocations in bcc MoNbTaW.…”
Section: Defects In the Presence Of High Chemical Disordermentioning
confidence: 99%
“…In this work, we present one possible application of our method: an efficient parameterization of material models that predict mechanical properties of a random alloy. More precisely, we parameterize the model for room temperature ductility of bcc random alloys from [28,34], which is based on the ratio of the K-factors for dislocation emission and cleavage, for the Mo-Nb-Ta medium-entropy alloy. This model was shown to be in good qualitative agreement with real experiments, and depends on the stacking fault energies on {112} planes, the {110} surface energies, and the elastic constants.…”
Section: Introductionmentioning
confidence: 99%
“…However, developing hydrogen storage materials with a low decomposition temperature and pressure (which are well suited for practical purposes), high recyclability, fast kinetics and high hydrogen storage capacity is one of the most crucial difficulties restricting the utilization of hydrogen energy for real applications [5][6][7]. Recently, high entropy alloys (HEAs), which are composed of five or more elements with atomic concentrations of 5-35% and tend to form single-phase solid solutions [8][9][10][11][12][13][14][15], have received much attention in the hydrogen storage field [16][17][18][19]. A number of investigations have suggested that hydrogen storage properties of HEAs can be enhanced by carefully tuning their constituents [17] and an excellent hydrogen storage performance can be achieved, like high hydrogen storage capacity [19,20], reversibly phase transformation [21], rapid hydrogen absorption [22] and moderate absorption/desorption temperature and pressure [23].…”
Section: Introductionmentioning
confidence: 99%